2003
DOI: 10.1034/j.1600-0714.2003.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic adenoma of the submandibular salivary glands with marked ossification

Abstract: This article describes an unusual case of pleomorphic adenoma arising in the submandibular salivary glands that was associated with marked ossification. CT scan showed an irregular high-density mass in the left submandibular region. Histologic examination of the resected mass revealed a well-circumscribed pleomorphic adenoma with chondroid tissue intermingled with glandular and trabecular epithelial components. Irregularly formed osseous tissue was present in the chondroid tissue. The osseous tissue showed bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Based on the immunohistochemical data in both normal salivary glands and pleomorphic adenomas, it was found that several particular VEGF signaling pathways may function not only in tumor cell proliferation but also in tumor cell arrangement. Our starting point of this study was the fact that pleomorphic adenoma is characterized by its poor vascularity in its stromal space whether it is hyaline, myxoid, or chondroid [12,17,19,29,37]. The poor vascularity in this particular tumor may be contrary to the general idea found in the textbook teaching which asserts that neoplastic tissues must be more vascularized than normal tissues [1].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Based on the immunohistochemical data in both normal salivary glands and pleomorphic adenomas, it was found that several particular VEGF signaling pathways may function not only in tumor cell proliferation but also in tumor cell arrangement. Our starting point of this study was the fact that pleomorphic adenoma is characterized by its poor vascularity in its stromal space whether it is hyaline, myxoid, or chondroid [12,17,19,29,37]. The poor vascularity in this particular tumor may be contrary to the general idea found in the textbook teaching which asserts that neoplastic tissues must be more vascularized than normal tissues [1].…”
Section: Discussionmentioning
confidence: 90%
“…These varieties of stromal phenotypes depend on the proportion of local contents of extracellular matrix molecules including basement membrane-associated molecules, such as perlecan, type-IV collagen, laminin, entactin, and fibronectin, which have been thought to be produced by tumor cells themselves [29]. Despite such a colorful histology, the stroma of pleomorphic adenoma is always poor in vascularity [12,37]. This is totally against the general idea of the highly vascular architectures of the neoplasm, on which anti-tumor therapeutic strategies have been devised [5].…”
Section: Introductionmentioning
confidence: 98%
“…The mucoid, myxoid, chondroid and hyaline materials seen in pleomorphic adenoma are generally interpreted as being products of myoepithelial cells. Meanwhile, typical ossification in pleomorphic adenoma is rare and only a few cases of pleomorphic adenoma with osseous tissue have been reported 5–8 . Moreover, although the mechanism of bone formation remains controversial, endochondral ossification 5–7 and metaplastic myoepithelial cells 8 have been reported as the ossification process.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive ossification in benign mixed tumours at any anatomical site is exceedingly rare 1–5 . Only four cases of pleomorphic adenoma with extensive areas of bone have been reported in published studies till date; we are reporting the fifth case 2–4 …”
mentioning
confidence: 87%